Distribution of Wetland Birds in Thamaraikulam Pond at Uthamapalyam Taluk, Theni District - Mrs.S.Devashanthi; Dr.Mrs.M.R.Delphine Rose (The Bioscan, 2025)
Wetland supports a variety of faunal diversity by providing them suitable habitat along with food and water. The present study investigates the species composition and diversity of wetland birds in Thamaraikulam Pond, situated in Gokilapuram village, Uthamapalayam Taluk, Theni District, Tamil Nadu, over a 12 month period from March, 2023 to February, 2024. Using standardized point count and transect methods a total of 3,873 individual birds belonging to 32 species were recorded. The dominant species included the Little Grebe (Tachybaptusruficollis) and Little Cormorant (Microcarboniger), while less frequent visitors included Black-necked Stork (Ephippior hynchusasiaticus) and Eurasian Spoonbill (Platalea leucorodia). Shannon-Weiner diversity index was calculated as 2.88 and the Margalef species richness index was 3.75 indicating moderate to high diversity. These findings highlight the ecological importance of the pond as a biodiversity hotspot and underline the need for continued monitoring and habitat protection amidst increasing anthropogenic pressures.